Flavin recognition by an RNA aptamer targeted toward FAD - Roychowdhury-Saha, Manami; Lato, Susan M; Shank, Eric D; Burke, Donald H (Biochemistry (Easton), 2002)
Flavin adenine dinucleotide (FAD) is one of the primary cofactors in biological redox reactions. Designing cofactor-dependent redox ribozymes could benefit from studies of new RNA-cofactor complexes, as would our understanding of ribozyme evolution during an RNA World. We have therefore used the SELEX method to identify RNA aptamers that recognize FAD. Functional analysis of mutant aptamers, S1 nuclease probing, and comparative sequence analysis identified a simple, 45 nt helical structure with several internal bulges as the core-binding element. These aptamers recognize with high specificity the isoalloxazine nucleus of FAD but do not distinguish FAD from FADH(2), nor are they removed from an FAD resin with UMP (which shares a pattern of hydrogen bond donors and acceptors along one face). Thus, these aptamers are structurally and functionally distinct from previously identified FMN and riboflavin aptamers. Circular dichroism data suggest a conformational change in the RNA upon FAD binding. These aptamers require magnesium and are active across a wide pH range (4.5-8.9). Since general acid-base catalysis plays a role in some flavin-dependent redox reaction mechanisms, these aptamers may be particularly well-suited to the design of new redox ribozymes.